Transmissivity as a Primary Metric for LNAPL Recovery—Case Study Comparison of Short‐Term vs. Long‐Term Methods. Issue 1 (17th December 2015) - Nagaiah, Manivannan; Law, Dennis R.; Ueland, Steven
Abstract : This article presents a case study and comparative analysis of light nonaqueous phase liquid (LNAPL) transmissivity estimated using short‐ and long‐term test methods at an active petroleum refinery. LNAPL transmissivity (Tn) is a recognized direct indicator of LNAPL recoverability with increasing acceptance by regulatory agencies. Historical releases at a refinery resulted in widespread LNAPL accumulations across the site and, as such, a focused approach is being implemented to enhance recovery, shorten remedial timeframes, and prioritize areas for recovery. Groundwater pumping systems operate continuously to maintain hydraulic containment of impacts, along with 12 LNAPL recovery systems. Transmissivity has been established as a primary metric and management tool for LNAPL recovery at the refinery. In this case study, estimated transmissivity values from short‐term data (baildown testing) and long‐term data (LNAPL skimming operations) from the same locations are analyzed and compared. Overall results are presented with respect to variations in transmissivities between the short‐ and long‐term tests, significance of data collection and quality, and consideration factors affecting transmissivity including fluid properties, soil types, hydrogeology, saturation levels, tidal effects, migration rates, and receptor risks. Additionally, the application of transmissivity as a metric for monitoring progress toward LNAPL recovery endpoints as part of the LNAPL remediation program development is discussed. ©2015 Wiley Periodicals, Inc.